Land capability evaluation for land use recommendation in Lawo watershed - Mahendra Harjianto; Naik Sinukaban; Suria Darma Tarigan; Oteng Haridjaja (Foresty Faculty of Hasanuddin University, 2016)
The changes of forest uses into agricultural land is a serious problem in Lawo watershed, South Sulawesi. Agricultural practices without implementing soil conservation and adequate agro-technology has caused high level of soil erosion and low land productivity. Management in Lawo watershed must be done with integrated soil and water conservation in order to increase agricultural production. This effort can be done with land capability evaluation. The purpose of this study is to evaluate the land capability of Lawo watershed using land capability category for data analysis. The results showed that Lawo watershed is dominated by land capability of class III with erosion (middle) as the dominant limiting factor which covers about 17,476.42 ha (49.68%). In addition, the class of land capability is followed by class IV with the slope (moderately steep) as the limiting factor and erodibility of soil (middle) covering about 10,059.8 ha (28.6%), land capability of class VI with slope (Steep) as the limiting factor with 7,638.32 ha (21.72%) coverage area. Land with class III can be recommended for dryland farming with adequate application of agro-technology, and water and soil conservation. While class IV and VI are not recommended for agricultural activities but for private forest or plantation forest.